2015
DOI: 10.1093/rpd/ncv474
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Iterative Reconstruction Enables the Evaluation of Thin-Slice Computed Tomography Images Without Degrading Image Quality or Increasing Radiation Dose

Abstract: Computed tomography (CT) is one of the most important modalities in a radiological department. This technique produces images that enables radiological reports with high diagnostic confidence, but may provide an elevated radiation dose to the patient. The radiation dose can be reduced by using advanced image reconstruction algorithms. This study was performed on a Brilliance iCT, equipped with iDose 4 iterative reconstruction and an iterative model-based reconstruction (IMR) method. The purpose was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
4
2
2
2
Order By: Relevance
“…A slight improvement in image quality for three out of five criteria in favor of the higher strength at 1 mm slice thickness was observed, when comparing the two algorithm strengths at same slice thickness and some dose reduction is possible. This could be attributed to the reduction in partial volume averaging [14] and/or increase in quantum noise in thinner slices [27]. Contrary to our study, two studies have reported retained image quality with thin slices for the higher strength of another MBIR [14,15].…”
Section: A Comparison Between Admire 5 Vs Admire 3 At 1 MM Slice Thcontrasting
confidence: 90%
See 2 more Smart Citations
“…A slight improvement in image quality for three out of five criteria in favor of the higher strength at 1 mm slice thickness was observed, when comparing the two algorithm strengths at same slice thickness and some dose reduction is possible. This could be attributed to the reduction in partial volume averaging [14] and/or increase in quantum noise in thinner slices [27]. Contrary to our study, two studies have reported retained image quality with thin slices for the higher strength of another MBIR [14,15].…”
Section: A Comparison Between Admire 5 Vs Admire 3 At 1 MM Slice Thcontrasting
confidence: 90%
“…This could be attributed to the reduction in partial volume averaging [14] and/or increase in quantum noise in thinner slices [27]. Contrary to our study, two studies have reported retained image quality with thin slices for the higher strength of another MBIR [14,15]. Both these studies evaluated effect of slice thickness using an iterative model-based reconstruction (Iterative Model Reconstruction (IMR), Philips) in brain CT and abdominal phantom respectively.…”
Section: A Comparison Between Admire 5 Vs Admire 3 At 1 MM Slice Thcontrasting
confidence: 63%
See 1 more Smart Citation
“…iDOSE provided, therefore, a similar image resolution to that obtained with FBP at significantly higher mAs values. Our results represent, therefore, a valuable confirmation that the use of IR algorithms preserves the spatial resolution while reducing mAs [ 21 ], except at very low tube load (i.e. < 50 mAs) where a very small decrease in spatial resolution was found [ 19 ].…”
Section: Discussionsupporting
confidence: 60%
“…There is a balance between the slice thickness and the amount of noise in the image. A previous study (21) showed that IMR could be used for analyzing images at thinner slice thicknesses, which improved image quality by suppressing the partial volume effect. Currently, IMR has been introduced in some routine examination protocols for adults in our clinic and images are analyzed in thin slices.…”
Section: Discussionmentioning
confidence: 99%